Language, knowledge, and growth: evidence from early modern Europe - Binzel, Christine; Link, Andreas; Ramachandran, Rajesh (SSRN, 2023)
This paper documents a language change in printing from Latin to the vernaculars, the spoken tongues, in the immediate aftermath of the Protestant Reformation of 1517. As a result, the share of vernacular titles in Europe rose from around 30% in 1500 to almost 60% in 1600. With the increased use of the vernaculars in printing, the availability of knowledge and ideas increased at the city level and became more diverse in terms of authors and themes. Finally, we study long-run consequences. Using linguistic differences across cities as a source of exogenous variation in the number of vernacular titles printed in cities, we document a positive effect of vernacular printing output on upper-tail human capital and city growth. This suggests that the turn to the vernaculars in printing was an important driver of European dynamism in the early modern period